The Australian drug harms ranking study. (July 2019) - Bonomo, Yvonne; Norman, Amanda; Biondo, Sam; Bruno, Raimondo; Daglish, Mark; Dawe, Sharon; Egerton-Warburton, Diana; Karro, Jonathan; Kim, Charles; Lenton, Simon; Lubman, Dan I; Pastor, Adam; et al.
Background/Aim: The aim of the current study was to review drug harms as they occur in Australia using the Multi-criteria Decision Analysis (MCDA) methodology adopted in earlier studies in other jurisdictions. Method: A facilitated workshop with 25 experts from across Australia, was held to score 22 drugs on 16 criteria: 9 related to harms that a drug produces in the individual and 7 to harms to others. Participants were guided by facilitators through the methodology and principles of MCDA. In open discussion, each drug was scored on each criterion. The criteria were then weighted using a process of swing weighting. Scoring was captured in MCDA software tool. Results: MCDA modelling showed the most harmful substances to users were fentanyls (part score 50), heroin (part score 45) and crystal methamphetamine (part score 42). The most harmful substances to others were alcohol (part score 41), crystal methamphetamine (part score 24) and cigarettes/tobacco (part score 14). Overall, alcohol was the most harmful drug when harm to users and harm to others was combined. A supplementary analysis took into consideration the prevalence of each substance in Australia. Alcohol was again ranked the most harmful substance overall, followed by cigarettes, crystal methamphetamine, cannabis, heroin and pharmaceutical opioids. Conclusions: The results of this study make an important contribution to the emerging international picture of drug harms. They highlight the persistent and pervasive harms caused by alcohol. Policy implications and recommendations are discussed. Policies to reduce harm from alcohol and methamphetamine should be a priority.